2018
DOI: 10.5194/esurf-2018-5
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Statistical modeling of the long-range dependent structure of barrier island framework geology and surface geomorphology

Abstract: 33Shorelines exhibit long-range dependence (LRD) and have been shown in some environments to 34 be described in the wavenumber domain by a power law characteristic of scale-independence. 35Recent evidence suggests that the geomorphology of barrier islands can, however, exhibit scale-36 dependence as a result of systematic variations of the underlying framework geology. The LRD of 37 framework geology, which influences island geomorphology and its response to storms and sea 38 level rise, has not been previousl… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…In the context of event data, exponential inter-event times are routinely assumed for mathematical and computational simplicity. However, many naturally occurring events, such as earthquakes (Ogata and Abe, 1991)), landscape evolution (Weymer et al, 2018)), and human brain activity (Tagliazucchi et al, 2013)), have been shown not to follow such patterns. We are also interested in identifying time periods when birds are more likely to sing and recovering groups of bird species that have similar singing patterns.…”
Section: Amazon Bird Vocalization Datamentioning
confidence: 99%
“…In the context of event data, exponential inter-event times are routinely assumed for mathematical and computational simplicity. However, many naturally occurring events, such as earthquakes (Ogata and Abe, 1991)), landscape evolution (Weymer et al, 2018)), and human brain activity (Tagliazucchi et al, 2013)), have been shown not to follow such patterns. We are also interested in identifying time periods when birds are more likely to sing and recovering groups of bird species that have similar singing patterns.…”
Section: Amazon Bird Vocalization Datamentioning
confidence: 99%